2001
DOI: 10.1161/01.atv.21.6.1084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute and Chronic Tea Consumption on Platelet Aggregation in Patients With Coronary Artery Disease

Abstract: Abstract-Epidemiological studies suggest that tea consumption is associated with a decreased risk of cardiovascular events, but the mechanisms of benefit remain undefined. Platelet aggregation is a precipitating event in cardiovascular disease, and tea contains antioxidant flavonoids that are known to decrease platelet aggregation in vitro. To test the effect of tea consumption on platelet aggregation, we randomized 49 patients with coronary artery disease to either 450 mL of black tea or water consumed initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 65 publications
0
52
1
2
Order By: Relevance
“…28 Because alcohol consumption also has antithrombotic activity, 29 our finding that tea consumption seems most protective among alcohol abstainers supports this as a possible mechanism. Whether the observed association between tea consumption and postinfarction survival reflects these physiological effects of tea or confounding by other factors associated with tea intake can only be answered in a large-scale, long-term randomized trial, although such a trial is unlikely to be performed in the near future.…”
Section: Mukamal Et Al Tea and Mortality After Myocardial Infarctionmentioning
confidence: 76%
“…28 Because alcohol consumption also has antithrombotic activity, 29 our finding that tea consumption seems most protective among alcohol abstainers supports this as a possible mechanism. Whether the observed association between tea consumption and postinfarction survival reflects these physiological effects of tea or confounding by other factors associated with tea intake can only be answered in a large-scale, long-term randomized trial, although such a trial is unlikely to be performed in the near future.…”
Section: Mukamal Et Al Tea and Mortality After Myocardial Infarctionmentioning
confidence: 76%
“…[23,24] The nitroglycerin portion of the study was omitted if systolic blood pressure was less than 100 mmHg, if the subject had a history of migraine headaches, or if he or she reported a previous history of prior adverse reaction to nitroglycerin. Ultrasound images (Powervision 6000, Toshiba Medical, Inc., Tustin, CA) were digitized online using customized hardware (Cardiovascular Engineering, Inc., Holliston, MA).…”
Section: Vascular Function Assessmentmentioning
confidence: 99%
“…Although some studies have found no lipidlowering effects from green or black tea consumption, most showed hypolipidemic effects for tea [213][214][215][216][217][218]. The association between tea drinking and lipid profile concentrations was linear for up to 10 cups per day, beyond which the association disappeared [219].…”
Section: Teamentioning
confidence: 96%